Immunity in cancer and atherosclerosis - Sima, Petr; Vannucci, Luca; Vetvicka, Vaclav (Annals of translational medicine, 2019)
Cancer and cardiovascular diseases have been classified as non-communicable diseases for decades. Both diseases have characteristics of immune reactions, which are principally identical, but differing in important aspects. The aim of this communication is to highlight new approaches to immune processes involved in both types of diseases.
Keywords: cardiovascular diseases; immunosurveillance; immunity; Cancer